Advancing virtual primary care for people with opioid use disorder (VPC OUD): a mixed-methods study protocol. Issue 9 (26th September 2022) - Hedden, Lindsay; McCracken, Rita K; Spencer, Sarah; Narayan, Shawna; Gooderham, Ellie; Bach, Paxton; Boyd, Jade; Chakanyuka, Christina; Hayashi, Kanna; Klimas, Jan; Law, Michael; McGrail, Kimberlyn; et al.
Abstract : Introduction: The emergence of COVID-19 introduced a dual public health emergency in British Columbia, which was already in the fourth year of its opioid-related overdose crisis. The public health response to COVID-19 must explicitly consider the unique needs of, and impacts on, communities experiencing marginalisation including people with opioid use disorder (PWOUD). The broad move to virtual forms of primary care, for example, may result in changes to healthcare access, delivery of opioid agonist therapies or fluctuations in co-occurring health problems that are prevalent in this population. The goal of this mixed-methods study is to characterise changes to primary care access and patient outcomes following the rapid introduction of virtual care for PWOUD. Methods and analysis: We will use a fully integrated mixed-methods design comprised of three components: (a) qualitative interviews with family physicians and PWOUD to document experiences with delivering and accessing virtual visits, respectively; (b) quantitative analysis of linked, population-based administrative data to describe the uptake of virtual care, its impact on access to services and downstream outcomes for PWOUD; and (c) facilitated deliberative dialogues to co-create educational resources for family physicians, PWOUD and policymakers that promote equitable access to high-quality virtual primary care for this population. Ethics and dissemination: Approval for this study has been granted by Research Ethics British Columbia. We will convene PWOUD and family physicians for deliberative dialogues to co-create educational materials and policy recommendations based on our findings. We will also disseminate findings via traditional academic outputs such as conferences and peer-reviewed publications.